THE ROLE OF EXPERIENCE MEDIATES THE INFLUENCE OF MOTIVATION AND SERVICE QUALITY ON THE INTENTION OF VISITING SPIRITUAL TRAVELERS TO BALI - Arya Adhitya Kusumaatmaja; Ni Wayan Ekawati; I Putu Gde Sukaatmadja; Putu Yudi Setiawan (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Bali remains the door to the world for Indonesia, although now the tourism industry is still completely paralyzed due to the Covid-19 pandemic, this period will gradually pass and Bali’s tourism situation will recover. Therefore, this study aims to determine what factors determine the intention of returning spiritual tourists to Bali. The method in this research is the quantitative method by path analysis (path analysis) using SPSS Statistics 23. The sample in this study amounted to 100 respondents where 56 domestic tourists and 44 people and tourists, were taken by using the technique. purposive sampling results showed that all the variables used in this study showed positive results, namely the intention to visit spiritual tourists to Bali again is influenced by spiritual motivation, quality of service either directly or through the mediation of experiences. The implication of this research is to provide an overview for the tourism industry players to take advantage of the moment when visitors arrive for the first time because this moment is used as an experience by them, providing qualities that will motivate them to come to visit again.